Characterization of Recombinant von Willebrand Factors Mutated on Cysteine 509 or 695 - Siguret, Virginie; Ribba, Anne-Sophie; Christophe, Olivier; Chérel, Ghislaine; Obert, Bernadette; Rouault, Christine; Nishikubo, Toshiya; Meyer, Dominique; Girma, Jean-Pierre; Piétu, Geneviève (Thrombosis and Haemostasis, 1996)
The interacting domain of vWF with platelet GPIb has been shown to overlap the large A1 loop formed by the intra-chain disulfide bond linking Cys 509 to Cys 695. In order to further investigate the role of the conformation of this region, we have expressed in COS-7 cells three mutated full-length recombinant vWFs (rvWFs) in which the substitutions Cys509Gly, Cys509Arg or Cys695Gly have been introduced by site-directed mutagenesis. SDS-agarose gel electrophoresis demonstrated an impaired multimerization of the mutants with undetectable high molecular weight multimers and a decrease of the relative amounts of the intermediate sized multimers. Binding analysis showed that rvWFC509G and rvWFC509R did not interact with botrocetin but spontaneously interacted with GPIb; the latter binding remained unchanged in the presence of ristocetin. This indicates that the substitution of Cys509 by Gly or Arg creates a conformation of vWF that increases its binding to GPIb. In contrast, rvWFC695G which did not react with botrocetin was also unable to interact with GPIb even in the presence of ristocetin, indicating that sequences interacting with GPIb are masked and/or disrupted. In conclusion, the substitution of each of the Cys509 and 695 results in mutant proteins which may be “locked” into active or inactive conformations in regard to the binding to platelet GPIb receptor.